Quorum sensing influences Vibrio harveyi growth rates in a manner not fully accounted for by the marker effect of bioluminescence. - Zeena E Nackerdien (Public Library of Science (PLoS), 2008)
Background The light-emitting Vibrios provide excellent material for studying the interaction of cellular communication with growth rate because bioluminescence is a convenient marker for quorum sensing. However, the use of bioluminescence as a marker is complicated because bioluminescence itself may affect growth rate, e.g. by diverting energy. Methodology/principal findings The marker effect was explored via growth rate studies in isogenic Vibrio harveyi (Vh) strains altered in quorum sensing on the one hand, and bioluminescence on the other. By hypothesis, growth rate is energy limited: mutants deficient in quorum sensing grow faster because wild type quorum sensing unleashes bioluminescence and bioluminescence diverts energy. Findings reported here confirm a role for bioluminescence in limiting Vh growth rate, at least under the conditions tested. However, the results argue that the bioluminescence is insufficient to explain the relationship of growth rate and quorum sensing in Vh. A Vh mutant null for all genes encoding the bioluminescence pathway grew faster than wild type but not as fast as null mutants in quorum sensing. Vh quorum sensing mutants showed altered growth rates that do not always rank with their relative increase or decrease in bioluminescence. In addition, the cell-free culture fluids of a rapidly growing Vibrio parahaemolyticus (Vp) strain increased the growth rate of wild type Vh without significantly altering Vh's bioluminescence. The same cell-free culture fluid increased the bioluminescence of Vh quorum mutants. Conclusions/significance The effect of quorum sensing on Vh growth rate can be either positive or negative and includes both bioluminescence-dependent and independent components. Bioluminescence tends to slow growth rate but not enough to account for the effects of quorum sensing on growth rate.